DISASTER MITIGATION BASED ON COMMUNITY INSTITUTIONS IN DISASTER-PRONE AREAS IN GARUT DISTRICT INDONESIA - Rd. Ahmad Buchari (Universitas Padjadjaran, 2021)
Demographically, Garut District is vulnerable to the occurrence of natural disasters due to the predominantly mountainous region. Disaster mitigation is the first step of prevention. Disaster mitigation conducted in Garut District was forming a disaster response village by using three aspects namely planning, institutional-level village and strengthening the community capacity as an effort to build a community resistance and responsive to the disaster. Institutional established in the village is useful to organize citizens to improve the awareness and social sense. While capacity building is a form of village, training resources to become volunteers whose focus is on entrepreneurship and disaster. The purpose of this research is to discover how disaster mitigation is based on community institutions in disaster-prone areas in Garut Regency. This study uses a qualitative approach by conducting sampling in three Disaster-resilient Villages, namely Pasawahan, Rancabango, and Karyamekar. This research uses observations, interviews and literature studies with analysis tools to see the village’s institutional in conducting disaster mitigation management with such aspects: 1) planning; 2) institutional; and 3) capacity building. The results show that disaster response training is not delivered optimally to citizens, and is still limited to volunteers established in each RT/RW. Therefore, the village government should increase the participation of citizens through training in all groups by planning and maximizing the disaster-resilient village with the institutional and capacity development both disaster volunteers and communities to reduce the loss of disaster and encourage villagers to conduct a green activity and maintain the environment to remain beautiful.